ANDROID APPLICATION FOR ISLAMIC CULTURAL HISTORY AND ITS ARTIFACTS BASED ON SPATIAL TECHNOLOGY - Amin, Meilan Khoirul; Fairuzabadi, Muhammad; Wahana, Aditya (CV. Fahr Publishing, 2025)
This study develops an Android application to enhance the learning of Islamic Cultural History for eighth-grade students at MTs Al Hijiriyah Sungai Lilin. The application aims to address the issue of low student interest caused by traditional teaching methods that are less engaging. Developed using the Waterfall model within the Software Development Life Cycle (SDLC), the application utilizes Flutter Dart as the programming language and MySQL as the database. The application is designed for two types of users: teachers and students. Teachers can upload and update materials through a web interface integrated with the application, ensuring that learning content remains relevant and engaging. This feature allows for more dynamic interaction between teachers and students and quicker content updates. Evaluation results show high user satisfaction, with 94% of respondents satisfied with the system's performance, and 91% appreciating the quality of the information provided. The application has proven effective in presenting Islamic Cultural History material in a more interactive and engaging way, thereby increasing students' interest in learning. Overall, the application offers a modern solution to the challenges of traditional teaching methods and contributes to the preservation of Islamic heritage through accessible technology.